PENGARUH CITRA RASA, CITRA MEREK, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN KOPI DI PT CENDANA HAN WIJAYA - Juwis Valantino; Inda Sukati (SCIENTIA JOURNAL, 2026)
This study aims to analyze the influence of taste image, brand image, and product quality on consumer purchasing decisions of coffee at PT Cendana Han Wijaya. The research employed a descriptive quantitative approach with data collected through a questionnaire distributed to 100 respondents who were consumers of PT Cendana Han Wijaya coffee products in Batam City. The sampling technique used was non-probability sampling. The collected data were analyzed using multiple linear regression analysis with the assistance of SPSS version 30, supported by validity tests, reliability tests, t-tests, and the coefficient of determination. The results indicate that taste image and product quality have a positive and significant effect on purchasing decisions, while brand image does not have a significant effect on purchasing decisions. Simultaneously, taste image, brand image, and product quality significantly influence consumer purchasing decisions. The Adjusted R Square value of 0.688 shows that 68.80% of the variation in purchasing decisions can be explained by the three independent variables, while the remaining percentage is influenced by other factors outside this study. These findings suggest that companies should prioritize improving taste consistency and product quality to enhance consumer purchasing decisions.